Effect of sodium butyrate supplementation on fattening guinea pig (Cavia porcellus) diets on the development of intestinal villi and crypts of Lieberkühn - Vallejos P., Diego (2015)
The aim of this study was to evaluate the effect of sodium butyrate supplementation on the development of intestinal villi and crypts of Lieberkühn in guinea pigs during the fattening period. A total of 45 male guinea pigs of 14 days of age (weaning age) were distributed in five treatments with nine repetitions per treatment: T1 was the control, T2 received zinc-bacitracin (200 ppm), and T3, T4 and T5 were supplemented with 100, 200 and 300 ppm of sodium butyrate respectively. The length and width of the villi, crypt of Lieberkühn depth and villus length and crypt depth ratio (L/D) in the duodenum, jejunumand ileum were evaluated at 84 days of age. In the length of intestinal villi, the duodenum T5 (0.812 mm) was larger than T1 (0.701 mm), also, T5 and T4 were larger than T3 (p <0.05). The width of ileum villi in T3 (0.114), T4 (0.115) and T5 (0.136 mm) were wider than T1 and T2 (p<0.05). The depth of the intestinal crypt in jejunum and ileum was smaller in T4 and T5 than T1 (p<0.05). The L/D ratio showed that T4 and T5 was higher than T0 in the three intestinal segments (p<0.05). The diet supplemented with sodium butyrate positively affected the intestinal development of guinea pigs during the fattening period as compared to the basal diet.